Blue-spotted stingray : A promising source of beneficial glycosaminoglycans (GAGs) - Marina, Mohd Sham; Nina Suhaity, Azmi (Research India Publication, 2016)
Glycosaminoglycans (GAGS) are polysaccharide composed of repeating disaccharide units either sulfated or non-sulfated monosaccharides of uronic acids and amino sugars which are structured alternately [1, 2]. As the sources of GAGs are mainly from the non-halal source and less extracted from halal source especially from marine lives, thus this invention is likely conducted in order to find the new halal source of GAGs. The objectives of the study are to extract the GAGs from Blue-spotted Stingray and characterize the extracted GAGs by using Blyscan assay, FTIR and NMR. The Blue-spotted stingray shows high sulfated GAG content which is 7.58% from crude obtained. Carboxylate with sulfate and amine presende in FTIR spectra indicate that the sample is chondroitin sulfate. The presence of O-sulfated group and methyl group of GalNAc and GlcNAc in NMR spectra indicate the presence of chondroitin sulfate. From the results, it can be concluded that GAGs contained in Blue-spotted Stingray.